2015
DOI: 10.1002/cmdc.201500141
|View full text |Cite
|
Sign up to set email alerts
|

Binding Mode of Acetylated Histones to Bromodomains: Variations on a Common Motif

Abstract: Bromodomains, epigenetic readers that recognize acetylated lysine residues in histone tails, are potential drug targets in cancer and inflammation. Herein we review the crystal structures of human bromodomains in complex with histone tails and analyze the main interaction motifs. The histone backbone is extended and occupies, in one of the two possible orientations, the bromodomain surface groove lined by the ZA and BC loops. The acetyl-lysine side chain is buried in the cavity between the four helices of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 39 publications
2
28
0
Order By: Relevance
“…Acetylation of N-terminal histone tails of H3 and H4 is a typical feature of transcriptional active chromatin and serves as a binding platform for epigenetic regulators, such as BET proteins (Davie and Candido, 1978; Dhalluin et al, 1999; Hebbes et al, 1988). It has been previously shown that the acetylation marks tested in this study are recognized by BET proteins (Marchand and Caflisch, 2015) and are involved in active gene expression (Morris et al, 2007; Wang et al, 2008). In addition, all tested acetylation marks except those of H3K14ac and H3K36ac were detected in spermatocyte nuclei, which indicated that tBRD-1 recognizes acetylated H3 at lysine 9 and/or 14 and acetylated H4 at lysine 5, 8, and/or 12 also in vivo .…”
Section: Discussionmentioning
confidence: 82%
“…Acetylation of N-terminal histone tails of H3 and H4 is a typical feature of transcriptional active chromatin and serves as a binding platform for epigenetic regulators, such as BET proteins (Davie and Candido, 1978; Dhalluin et al, 1999; Hebbes et al, 1988). It has been previously shown that the acetylation marks tested in this study are recognized by BET proteins (Marchand and Caflisch, 2015) and are involved in active gene expression (Morris et al, 2007; Wang et al, 2008). In addition, all tested acetylation marks except those of H3K14ac and H3K36ac were detected in spermatocyte nuclei, which indicated that tBRD-1 recognizes acetylated H3 at lysine 9 and/or 14 and acetylated H4 at lysine 5, 8, and/or 12 also in vivo .…”
Section: Discussionmentioning
confidence: 82%
“…Our proposed role for Trp1338 is corroborated by its prominent location at the intersection of two roughly perpendicular grooves that are poised to accommodate bound peptides. The first groove is hydrophobic and extends above the canonical N-acetyllysine binding pocket between the ZA and BC loops, which corresponds to the preferred peptide binding groove in experimentally determined bromodomain-peptide complexes ( Figure 3E) (Fujisawa and Filippakopoulos, 2017;Marchand and Caflisch, 2015;Zeng et al, 2008). The second groove is slightly negatively charged and is formed between the βhairpin and a surface patch formed by Trp1338 and Asp1267.…”
Section: Discussionmentioning
confidence: 85%
“…Both hydrogen bonds are present in all crystal structures of BAZ2A/B reported in this work, as well as in those previously disclosed with the exception of the complex between BAZ2B and 6‐hydroxyindole in which the NH of the ligand replaces the water W1 (PDB ID: https://www.rcsb.org/structure/5E9I). The scatter plot in Figure a shows that the distance to the bridging water is shorter than the distance to the side chain of the conserved asparagine for all compounds (except for the acetylindole derivative 8 ) in agreement with previous reports . Interestingly, the hydrogen bond lengths can be clustered on the basis of the chemical class of the compounds independently of the bound bromodomain.…”
Section: Resultsmentioning
confidence: 99%
“…ChemMedChem 2018ChemMedChem , 13,1479ChemMedChem -1487 www.chemmedchem.org 2018 Wiley-VCH Verlag GmbH &Co. KGaA, Weinheim distance to the bridging water is shorter than the distance to the side chain of the conserved asparaginef or all compounds (except fort he acetylindole derivative 8)i na greement with previousr eports. [14,19,20] Interestingly,t he hydrogenb ond lengths can be clustered on the basis of the chemical class of the compounds independently of the bound bromodomain. The distance to the structurally conserved water reflectst he degree of burial of the compounds (Figure 3b).…”
Section: Comparison Of Binding Modesmentioning
confidence: 99%